Perspepsi Guru Terhadap Penggunaan Media Grafis dalam Meningkatkan Keterampilan Berbicara Siswa Sekolah Dasar - Taura Meldini; Rahma Vanessa; Rafi Hibrizi; Sartono Sartono (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study investigates teachers' views on utilizing graphic media to enhance the speaking abilities of elementary school students. Employing a qualitative approach with a literature review, the study analyzes various journals, books, and relevant scientific articles. Findings reveal that teachers generally hold a favorable attitude toward graphic media, as it helps simplify material comprehension and motivates students to engage more actively in speaking activities. Nonetheless, challenges remain, including limited access to resources and insufficient technological skills. The discussion highlights the necessity of providing teacher training and institutional support to maximize the use of graphic media. In summary, graphic media proves to be an effective tool for improving speaking skills when combined with appropriate strategies and adequate teacher expertise.